UNDERSTANDING LIVESTREAMING SHOPPING: A SYSTEMATIC LITERATURE REVIEW - Rakhmanita, Ani; Fahruri, Arief; Ikhsan, Muhammad (MSJ : Majority Science Journal, 2025)
Livestreaming presents itself as a new form of shopping environment that stimulates potential consumers in making stimulated shopping decisions. This paper aims to review the development of research related to livestreaming shopping using computational bibliometric analysis. Publish or Perish software was used to obtain literature data using the keyword "livestreaming shopping" and selecting a search database on Google Scholar with a time limit used for the last 10 years (2014 to 2024). The initial data search results were 457 articles, then filtered by removing documents deemed less relevant to the specified keywords/titles. The results show that livestreaming shopping research can be divided into two terms, namely live commerce and livestreaming shopping. The results of the analysis of livestreaming shopping publications in the last 10 years show an increase in the number of publications each year. The highest number of publications was in 2024 with 114 articles and the smallest publications in 2014 with 10 articles. This bibliometric analysis provides a summary and potential avenues for future livestreaming shopping research, as suggested by the findings